Prognostic assessment of processes of formation of high professional suitability of students purchasing the specialties of rehabilitation profile (Environment & Health, 2025)
The aim of the study was to justify the methodology of comprehensive prognostic assessment of the processes of formation of high professional suitability of students who acquire specialties of rehabilitation specialists, taking into account the degree of development of professionally important psychophysiological functions and personality traits.Research materials and methods. The research was conducted on the basis of National Pirogov Memorial Medical University, Vinnitsya. A complex of hygienic, psychophysiological and psychodiagnostic methods, methods of statistical analysis and expert evaluations was used to realize the set goal.The results. In the course of research, it was determined that the main stages of the practical interpretation of the methodology of complex prognostic assessment of the processes of formation of high professional suitability of students who acquire specialties of the rehabilitation profile are: determination on the basis of the application of modern instrumental and test (computerized) methods of the degree of expression of the leading professionally important psychophysiological personality functions and personality traits (diagnostic stage); evaluation of the obtained data in standardized points in accordance with specially created point-based assessment scales of the level of development of psychophysiological functions and personality traits according to psychophysiological and personal loci (standardization stage); calculation, according to generalized formulas, of the success rates of the processes of forming the professional fitness of students who acquire the specialties of a doctor of physical and rehabilitation medicine, a physical therapist and occupational therapist, assistant of a physical therapist and assistant of an occupational therapist (calculation stage). evaluation of the peculiarities of the process of formation of professional suitability of students, based on the application of quantitative criteria of meaningful assessment (interpretation stage); determination of individualized strategies for the use of means of psychophysiological influence and psychohygienic correction of deviations that occur (correction stage).Conclusions. In the course of the research, a scientifically based complex prognostic assessment method was developed based on the degree of development of psychophysiological functions and personality characteristics, which provides an opportunity to determine the peculiarities of the course of the processes of psychophysiological and mental adaptation of students who acquire specialties of rehabilitation specialists.
Keywords: students; institution of higher education; professional suitability; rehabilitation; psychophysiological functions; personality traits